Ocupação e padrões de atividades de mamíferos de médio e grande porte em um mosaico de Mata Atlântica e plantações de eucalipto - Richard Hatakeyama (2015)
The Atlantic Forest is one of the most threatened Brazilian biomes, constantly being fragmented and replaced by forestry. At Minas Gerais state, part of this replacement is made by commercial plantations or eucaliptus reforestation. Studies shows that eucalyptus plantations can be used as a habitat by innumerous mammals species, but the whole landscape is generally not analyzed. This study verified the importance of eucalyptus plantations on the occupancy of medium and large sized terrestrial mammals in relation to a close by native forest, the Rio Doce State Park, in addition to verify what environmental variables affects this animals occupancy on the landscape the most, like the proportion of native vegetation and eucalyptus, distance to the park and water resource. Only the agouti (Dasyprocta azarae) had a negative relation to the proportion of eucalyptus plantations highlighted, being the presence of water resources the most determinant factor on the occupancy of the other mammals species. Lastly, its not recommended the replacement of any native forest by eucalyptus plantations, yet its believed to be plausible the sustenance of this existing plantations when associated whit large forested areas, since the majority of the mammals fauna seems to use them frequently.